Isolated guinea pig gastric chief cells express tumour necrosis factor receptors coupled with the sphingomyelin pathway. (February 1996) - Fiorucci, S; Santucci, L; Migliorati, G; Riccardi, C; Amorosi, A; Mancini, A; Roberti, R; Morelli, A
Abstract : The tumour necrosis factor alpha (TNF), has been implicated in the pathogenesis of non-steroidal anti-inflammatory drug (NSAID) induced gastropathy and Helicobacter pylori induced gastritis. Both conditions are characterised by high plasma pepsinogen concentrations, which are thought to reflect an increased rate of enzyme release by the pepsinogen secreting (chief) cells. The mechanisms responsible for this cell dysfunction are unknown. This study investigates whether chief cells express TNF receptors and, if so, whether their activation results in cell death. Immunohistochemical studies conducted with monoclonal antibodies (mAbs) directed against two TNF receptor associated proteins of 55 kDa (TNF-R1) and 75 kDa (TNF-R2) showed that TNF binding sites were expressed in approximately 100% gastric chief cells. Western blot analysis of whole chief cell lysates probed with the TNF-R1 and TNF-R2 mAbs gave two distinct bands of 55 and 75 kDa in the immunoprecipitate. Incubating chief cells with TNF caused concentration and time dependent cell death, which was prevented by pretreating the cells with anti-TNF receptor mAbs. Exposing the cells to TNF reduced sphingomyelin content by 25%. Sphingomyelinase (10(-6) to 10(-2) IU/ml) mimicked the effect of TNF in that it provoked a concentration and time dependent reduction in chief cell viability and increased pepsinogen release. In conclusion, gastric chief cells express two TNF receptors partially linked to the sphingomyelin pathway. TNF induced chief cell dysfunction might be responsible for the high plasma pepsinogen concentrations seen in patients with NSAID gastropathy or H pylori induced gastritis.